Analysis and Solution of Signal Compatibility for AC Diesel Locomotive - XIAO Gongbin (Kongzhi Yu Xinxi Jishu)
It described the compatibility problems of AC drive diesel locomotives in the process of track signal system interference test. The compatibility requirements between locomotive track current and signal system were introduced and the forming mechanism of the locomotive track interference current and the influencing factors were analyzed. The improvement methods were also presented, such as the control strategy of traction converter; the control mode of the drive system and the shielding increment of the traction motor to reduce the track interference current in the process of locomotive signal compatibility. The improved methods were proved effectively which could solve the signal interference problems.